The Ageing of the New Zealand Population, 1881-2051 - John Bryant (New Zealand Government, The Treasury, 2003)
The paper reviews data on long-term changes in the age structure of the New Zealand population. It sets out trends and projections for the age structure of the national population, and for associated measures of dependency. It describes the influences on age structure of fertility, mortality, and migration. Disaggregated results on age structure are presented, including ethnic differentials, regional variations, and fluctuations within narrowly-defined age groups. Comparisons are made with other OECD countries. Uncertainty, the likelihood of continued life expectancy gains, and life expectancy and health at older ages are discussed.
Keywords: J11; J14; 330; Population Ageing; New Zealand; Demographic Trends